National Ignition Facility Laser System Performance. (1st February 2016) - Spaeth, Mary L.; Manes, Kenneth R.; Bowers, M.; Celliers, P.; Nicola, J.-M. Di; Nicola, P. Di; Dixit, S.; Erbert, G.; Heebner, J.; Kalantar, D.; Landen, O.; MacGowan, B.; et al.
Abstract: The National Ignition Facility (NIF) laser is the culmination of more than 40 years of work at Lawrence Livermore National Laboratory dedicated to the delivery of laser systems capable of driving experiments for the study of high-energy-density physics. Although NIF was designed to support a number of missions, it was clear from the beginning that its biggest challenge was to meet the requirements for pursuit of inertial confinement fusion. Meeting the Project Completion Criteria for NIF in 2009 and for the National Ignition Campaign (NIC) in 2012 included meeting the NIF Functional Requirements and Primary Criteria that were established for the project in 1994. During NIC and as NIF transitioned to a user facility, its goals were expanded to include requirements defined by the broader user community as well as by laser system designers and operators.